STUDI LITERATUR: KESULITAN BELAJAR MATEMATIS SISWA KELAS VII SMP PADA MATERI HIMPUNAN - Ramadina, Novia Isnaini; Fuat; Afifah, Ani; Lutfiah, Ainul (IAIN Pontianak, 2025)
This study aims to conduct a literature review related to junior high school students' mathematical learning difficulties in the set material. The method used in the study is Literature Study. The sample consists of several articles in journals. Data collection is carried out through the process of searching, learning, and analyzing references from relevant results related to students' understanding of mathematical concepts, reviewed from the year of research, level of education, research results and type of research. Based on the results of this literature study, it shows that students' mathematical understanding in solving mathematical problems on the set material is still prone to errors and misunderstandings. Some obstacles that often arise include shallow understanding of the definition and basis of sets, difficulty in applying set operations, and difficulty in understanding the concept of relations between sets at all levels. Further research is needed to understand in depth the conditions that affect students' mathematical understanding in the set material. In addition, the development of effective learning strategies also needs to be done to help students gain a better mathematical understanding in solving mathematical problems on the set material. This study identifies the causes of junior high school students' mathematical learning difficulties in the set material, such as lack of understanding of basic concepts, lack of practice and experience in applying the material. The results of this literature study can provide information and guidance for mathematics teachers to improve junior high school students' mathematics learning on the subject of sets.